Comparative Whole-Genome Analysis of Production Traits and Genetic Structure in Baiyu and Chuanzhong Black Goats - Jing Luo; Qi Min; Xueliang Sun; Xinyu Guo; Meijun Song; Xuehui Zeng; Jiazhong Guo; Hongping Zhang; Yanguo Han; Li Li (Animals)
Natural selection and artificial breeding are crucial methods for developing new animal groups. The Baiyu black goats and Chuanzhong black goats are indigenous goat breeds from distinct ecological regions in Sichuan Province, with dramatically different growth and reproductivity. This study aimed to systematically elucidate the differences in production performance and genetic traits between Baiyu black goats and Chuanzhong black goats. We quantified growth and reproductive attributes for both breeds. Furthermore, we conducted a comprehensive analysis of genetic diversity, population structure, and selection signatures using whole-genome resequencing data. This dataset included 30 individuals from the Baiyu black goat breed, 41 from the Chuanzhong black goat breed, and an additional 59 individuals representing Chengdu grey goats, Tibetan cashmere goats, and Jianchang black goats, totaling 130 individuals across five goat breeds. The comparative analysis of production performance revealed that the weight and body size of Chuanzhong black goats were significantly higher than those of Baiyu black goats (p < 0.01). At the same time, the average kidding rate and kid-weaning survival rate of Chuanzhong black goats were also notably superior to those of Baiyu black goats (p < 0.01). The Baiyu black goats exhibited a more abundant genetic diversity and distinct genetic differences compared to the Chuanzhong black goat, according to an analysis grounded on genomic variation. The Baiyu black goats are more closely related to Tibetan cashmere goats, whereas Chuanzhong black goats share a closer genetic relationship with Chengdu grey goats. Additionally, we employed the π, Fst, and XP-EHH methodologies to identify genes related to immunity (TRIM10, TRIM15, TRIM26, and TRIM5), neurodevelopment (FOXD4L1, PCDHB14, PCDHB4, PCDHB5, PCDHB6, and PCDHB7), reproduction (BTNL2 and GABBR1), body size (NCAPG, IBSP, and MKNK1), and meat quality traits (SUCLG2 and PGM5). These results provide a theoretical basis for further resource conservation and breeding improvement of the Baiyu black goat and Chuanzhong black goat.